Comparative in vitro activities of clarithromycin, azithromycin, and erythromycin against Borrelia burgdorferi. - Dever, L L (1993)
The in vitro activities of the macrolide antibiotics clarithromycin, 14-hydroxy-clarithromycin, azithromycin, and erythromycin against 19 isolates of Borrelia burgdorferi were investigated. MICs ranged from 0.003 to 0.03 microgram of clarithromycin per ml, 0.007 to 0.03 microgram of 14-hydroxyclarithromycin per ml, 0.003 to 0.03 microgram of azithromycin per ml, and 0.007 to 0.06 microgram of erythromycin per ml. Time-kill studies using the B31 strain of B. burgdorferi demonstrated a > or = 3-log10-unit killing after 72 h with each of the macrolide antibiotics tested in concentrations representing twice the respective MICs.